monthly probabilities for acquiring remote sensed data of indonesia with cloud cover less than 10 , 20 and 30 percent - J.P. Gastellu- Etcregorry (Indonesian Journal of Geography, 1988)
The Indonesian spatiotemporal cloud cover distribution was quantified with the aid of GMS, Landsat and SPOT data. Iterative interactive factorial analyses grouped pixels with similar profiles into 18 classes for all land areas. For each class, statistics of Landsat and SPOT images, grouped by class, were used to verify, calibrate and improve class profiles. This led to quantified temporal profiles of probability of acquiring remotely sensed data with 10 , 20 and 30 percent cloud cover, for any Indonesian land area.